“Influencia de la musicoterapia como metodo psicoprofilactico en la duracion del trabajo de parto” Hospital regional del norte – PNP. CAP. “Jose A. Quiñones Gonzales” - Chiclayo – Octubre1996 – Julio 1997” - Silva Mejia, Diana Elena (2000)
With the general aim of detenninar the influence of music therapy as a method Psicoprofiláctico in the decrease of labour, is realiz.o this research in pregnant women who came to control pre natal consultation to the Regional Hospital in the North of the PNP CAP "José a. Quiñones Gonlalez" of Chiclayo, during the period from October 1996 to July 1997. The research was quasi - experimental and longitudinal. The design of verification of the hypothesis used was the of trial clinical controlled. The groups were homogeneous, with respect to age, marital status, degree of instruction and parity. The sample consisted of 35 pregnant women, captured from the 28 weeks of gestation and that they formed the experimental application of music therapy group, and 35 women formed the group control (without application of music therapy). Highlighting that it was used in the hands-on music both in the gym and relaxation. 7 between the major...